Influence of sub-lethal HcH on differential distribution of dehydrogenases, glycogen, pyruvate and lactate in different brain regions in Labeo rohita (Ham). - Shaffi, S A (Indian Journal of Fisheries, 2011)
Sub-lethal impact of HcH was investigated on differential distribution of LDH,MDH, SDH, glycogen, pyruvate and lactate in different brain regions (cerebrum,diencephalon, cerebellum and medulla oblongata) in L. rohita (Ham.) under acute,chronic and recovery situations. Rise in dehydrogenases in early stage of acuteand chronic studies to a maximum extent in cerebrum than the remaining brainregions was recorded. During recovery studies, elevation in LDH, MDH, SDH,glycogen and pyruvate and fall in lactate in different brain regions (fast in cerebellumand slow in cerebrum) in L.rohita were noticed. The observed changesduring acute, chronic and recovery studies are discussed in detail.